2023
DOI: 10.1094/phyto-06-22-0203-r
|View full text |Cite
|
Sign up to set email alerts
|

The Expanding Menagerie of Prunus-Infecting Luteoviruses

Abstract: Members of the genus Luteovirus are responsible for economically destructive plant diseases worldwide. Over the past few years, three luteoviruses infecting Prunus trees have been characterized. However, the biological properties, prevalence, and genetic diversity of those viruses have not yet been studied. High throughput sequencing of samples of various wild, cultivated, and ornamental Prunus species enabled the identification of four novel species in the genus Luteovirus for which we obtained complete or ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The P3a-like protein was also not identified in BlVL, AlLV1, NSPaV, RCaV, or PmaLV. However, PmaLV does encode the P4 movement protein ( Khalili et al., 2023 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The P3a-like protein was also not identified in BlVL, AlLV1, NSPaV, RCaV, or PmaLV. However, PmaLV does encode the P4 movement protein ( Khalili et al., 2023 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Analyses included isolates of 19 genomes, with REFSEQ isolates used where available; the 13 luteoviruses accepted by ICTV and six putative unclassified members of the genus: almond luteovirus 1 (AlLV1), peach associated luteovirus (PaLV) and four Prunus -infecting species ( Khalili et al., 2023 ). NCBI ORFfinder and alignments to other luteoviruses was used to identify BlVL ORFs.…”
Section: Methodsmentioning
confidence: 99%
“…), usually through infected pollen (Bristow and Martin 1999). Ilarviruses pose persistent threats to fruit production such as for Prunus species (Pallas et al 2012;Khalili et al 2022) or blackberry (Rubus fruticosus) (Poudel et al 2014). In recent years, several ilarviruses were reported to cause problems in tomato production in the USA, such as tomato necrotic streak virus (TomNSV) (Badillo-Vargas et al 2016;Adkins et al 2015) and tomato necrotic spot virus (ToNSV) (Bratsch et al 2019(Bratsch et al , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mining of vast amounts of Arabidopsis thaliana publicly available sequence read archive (SRA) datasets uncovered a novel comovirus (family Secoviridae ), Arabidopsis latent virus 1, which was demonstrated to be mechanically and seed transmitted, but causes no symptoms in A. thaliana , (Verhoeven et al 2022). A recent study on Prunus -associated luteoviruses (family Luteoviridae ) also uncovered a new luteovirus through a search of SRA datasets (Khalili et al 2022). Many HTS-based discoveries of crop and non-crop viruses have also been reported (Gaafar et al 2020; Rivarez et al 2022; Ma et al 2019; Xu et al 2017), but only a small subset of these studies biologically characterized the identified viruses (Hou et al 2020; Rivarez et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The large contigs representing the two genomic RNAs of ALRSV and MLRSV missed only short terminal sequences. Both 5' and 3' genome ends were determined for each molecule by RACE experiments as described [7]. Full-length RNA1 were determined to be 7,690 nt (OR141117) and 7,678 nt (OR141115), excluding the polyA tail, for ALRSV and MLRSV respectively, while their RNA2 were respectively 5,686 nt (OR141118) and 5,736 nt (OR141116).…”
mentioning
confidence: 99%